2019
DOI: 10.2147/copd.s213364
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association among genetic polymorphisms of GSTP1, HO-1, and SOD-3 and chronic obstructive pulmonary disease susceptibility</p>

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a progressive lung disease characterized by incomplete reversible airflow limitation, which is associated with emphysema and chronic inflammation. Oxidative/antioxidant imbalance is one of the mechanisms of the current pathogenesis of COPD and several recent studies have attempted to uncover genetic causes of COPD and its progression. GST, HO-1, and SOD-3 are important susceptibility genes related to COPD.MethodsA total of 300 blood samples were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Heme oxygenase (HMOX1) is a key enzyme that catalyzes the rate-limiting first step in the heme degradation process, generating carbon monoxide, ferrous and biliverdin, and therefore HMOX1 has a cytoprotective role as excess free heme has been shown to induce apoptosis [ 27 ]. HMOX1 is expressed at high levels in the lungs and has been shown to mediate anti-inflammatory effect of interleukin-10 (IL-10) in mice [ 68 , 69 ]. Given these functions of HMOX1, it has been implicated in a variety of pathological states, including myocardial infarction, diabetes, chronic obstructive pulmonary disease (COPD) [ 69 , 70 ].…”
Section: Role Of Hmox1 In Thrombosis Fibrinolysis and Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Heme oxygenase (HMOX1) is a key enzyme that catalyzes the rate-limiting first step in the heme degradation process, generating carbon monoxide, ferrous and biliverdin, and therefore HMOX1 has a cytoprotective role as excess free heme has been shown to induce apoptosis [ 27 ]. HMOX1 is expressed at high levels in the lungs and has been shown to mediate anti-inflammatory effect of interleukin-10 (IL-10) in mice [ 68 , 69 ]. Given these functions of HMOX1, it has been implicated in a variety of pathological states, including myocardial infarction, diabetes, chronic obstructive pulmonary disease (COPD) [ 69 , 70 ].…”
Section: Role Of Hmox1 In Thrombosis Fibrinolysis and Sepsismentioning
confidence: 99%
“…HMOX1 is expressed at high levels in the lungs and has been shown to mediate anti-inflammatory effect of interleukin-10 (IL-10) in mice [ 68 , 69 ]. Given these functions of HMOX1, it has been implicated in a variety of pathological states, including myocardial infarction, diabetes, chronic obstructive pulmonary disease (COPD) [ 69 , 70 ]. Upregulation of HMOX1 has been shown to have a protective role against the oxidative stress produced upon HIV, DENV, HCV, and IAV infections [ 71 ].…”
Section: Role Of Hmox1 In Thrombosis Fibrinolysis and Sepsismentioning
confidence: 99%
“…From this study, it may be concluded that Ho-1 gene polymorphism has an important role in coPd. Yamada et al (52), du et al (78) and Zhou et al (79) also demonstrated that the L (GT)n allele frequency in patients with coPd was significantly higher compared with that in the control group.…”
Section: Association Between Ho-1 Gene Polymorphism and Clinical Diseasesmentioning
confidence: 94%
“…In continuous research in recent years, the polymorphism of the HO-1 gene promoter has been found to have a certain correlation with a growing number of disease states. In a deal of past clinical work, the association between (GT)n repeat length polymorphism and the risk of various diseases has been reported, including respiratory system diseases [ 104 ], malignant tumor [ 105 , 106 ], and others. The epidemiological correlation may be used as a risk index to evaluate the susceptibility and prognosis of the disease, and also be beneficial to the study of disease pathogenesis and potential therapeutic targets.…”
Section: Possible Assessment Markers For Diseasementioning
confidence: 99%